Insilico Analysis of Cranberry Proanthocyanidin Epicatechin (4beta-8,2beta-0-7) as an Inhibitor for Modelled Afimbrial Adhesin Virulence Protein of Uropathogenic Escherichia Coli - Abhilash M (International Journal of Pharma and Bio Sciences, 2010)
Fimbrial adhesion is a Virulence Determinant which is classified under Adhesins category of virulence factor of uropathogenic Escherichia coli. Afimbrial adhesin Protein with swissprot accession number P12730, of length 181 amino was selected for modeling using Bioinformatics tools. Modelled protein has been submitted to protein model database and has been assigned an accession number of PM0075877. Docking analysis of Epicatechin(4beta-8,2beta-0-7), a Proanthocyanin from cranberry against modelled fimbrial adhesion was carried out using hex docking tool. Some of the commonly used antibiotics to treat urinary tract infections caused by Uropathogenic E.coli which includes Oflaxacin, sulfamethoxazole, Trimethoprim were subjected to docking analysis for comparative studies.